1994
DOI: 10.1109/87.294335
|View full text |Cite
|
Sign up to set email alerts
|

Review of the damped least-squares inverse kinematics with experiments on an industrial robot manipulator

Abstract: The goal of this paper is to present experimental results on the implementation of the damped least-squares method for the six-joint ABB IRb2000 industrial robot manipulator. A number of inverse kinematics schemes are reviewed which allow robot control through kinematic singularities. The basic schemes adopts a damped least-squares inverse of the manipulator Jacobian with a varying damping factor acting in the neighbor-hood of singularities. The effect of a weighted damped least-squares solution is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(162 citation statements)
references
References 24 publications
(13 reference statements)
0
146
0
3
Order By: Relevance
“…9 and Eq. 13, respectively, are effective methods to perform trajectory conversion from taskspace to joint-space [16]. To a certain degree, the null space terms can be designed to perform secondary objectives such as keeping the robot away from kinematic constraints.…”
Section: Handling Kinematic Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 and Eq. 13, respectively, are effective methods to perform trajectory conversion from taskspace to joint-space [16]. To a certain degree, the null space terms can be designed to perform secondary objectives such as keeping the robot away from kinematic constraints.…”
Section: Handling Kinematic Constraintsmentioning
confidence: 99%
“…where K is a positive definite gain matrix and the vector e describes the orientation and position error between the desired and computed task descriptors [1], [16]:…”
Section: A Velocity-based Controlmentioning
confidence: 99%
“…The pseudo inverse method replaces the Jacobian by its pseudo inverse, while it is not the exact inverse of J is still a good approximation. The main challenge with Jacobian inverse methods is how to compute to compute the Jacobian iteratively (Chiaverini et al, 1994;Buss, 2004).…”
Section: Inverse Kinematicsmentioning
confidence: 99%
“…The second class includes nature inspired techniques and hybrid techniques with learning capacities such as neural networks and neuro-fuzzy systems (Rutkowski et al, 2012;Juang, 2000;Zaidi et al, 2012;Pérez-Rodríguez et al, 2012) where the IK solver is observed as system with a set of inputs and output(s), the system needs first to be trained using a set of targets and solutions generally obtained using the forward kinematic model, it is then validated with a separate validation set and finally used. When the target point is far from the training set this systems generate limited precision solutions compared to Jacobian based conventional methods (Chiaverini et al, 1994;Buss, 2004); they are also time consuming and can not satisfy real time constraints (Zaidi et al, 2013;Pérez-Rodríguez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation